PENGARUH KINERJA KEUANGAN TERHADAP ALOKASI BELANJA MODAL PEMERINTAH DAERAH DI KABUPATEN DAN KOTA PROVINSI SUMATERA BARAT TAHUN 2013 – 2017 - Muhammad Arif; Fefri Indra Arza (STIE Atma Bhakti, 2018)
The purpose of this study was to determine the effect of regional financial independence, effectiveness of PAD, efficiency of regional expenditures and harmony of expenditure on the allocation of capital expenditure. The sample used in this study is the entire population, namely 19 regencies / municipalities covering 12 regencies and 7 municipalities in West Sumatra Province. The research period is 2013-2016, so the total sample data is 76 sample data. The analysis is carried out using Eviews 8. The results of testing of the four factors that influence the allocation of capital expenditures show that regional financial independence and effectiveness of PAD do not affect the allocation of capital expenditure, while regional financial efficiency and harmonious regional expenditure have a significant positive effect on the allocation of capital expenditure . Keywords: Regional Financial Independence, Effectiveness, Local Revenue, Efficiency of Regional Expenditures, Harmony of Expenditures and Allocation of Capital Expenditures.